KIBLAT DIRECTION ACCURACY TAKES CORRELATION BETWEEN SUN AZIMUTH WITH AZIMUTH MOTION VIGNA RADIATA - Saiyed Amar Achmad; Fatmawati Hilal (HISABUNA: Jurnal Ilmu Falak, 2020)
The main problem in this study is how to test the accuracy of Qibla direction utilizing the correlation between the solar azimuth and the azimuth of the vigna radiata. The subject matter is further divided into 1) What is the relationship between the direction produced by motion in the vigna radiata plant and the solar azimuth? 2) How accurate is the Qibla direction measurement using the correlation between solar azimuth and green bean azimuth ?. The hypothesis of this study is that there is a relationship between the direction of motion of green beans on the sun's azimuth that can be tested for the accuracy of the Qibla direction.The theoretical basis used in this research is spherical trigonometry with the method of measuring the Qibla direction utilizing the sun's azimuth and the theory of motion in plants.This type of research is experimental research - quantitative field research. The approach in this study uses a shar'i, scientific and mathematical approach. The population that researchers took for this study were 30 green bean plants with saturated samples. Data collection methods used in this study are the method of observation and documentation. The researcher conducted the analysis using the comparative analysis method with the verification work process.The results obtained in this study are that there is a match between the azimuth of the mungbean and the sun azimuth at a certain time interval, which is around 11 noon for the first sample and around 3 pm for the second sample. After being tested between the two azimuths there was a maximum inclination of 6 ° and 7 ° with an average inclination of 1.19 ° and 1.47 °. If the plant azimuth is used directly to measure the Qibla direction without correlation to the sun's azimuth it will produce a value of a large enough slope of 127 ° 23'54.61 "in sample 1 and 107 ° 8'54.61" in sample 2.